p53 Regulation of G(2) Checkpoint Is Retinoblastoma Protein Dependent - Flatt, Patricia M. (American Society for Microbiology, 2000)
In the present study, we investigated the role of p53 in G(2) checkpoint function by determining the mechanism by which p53 prevents premature exit from G(2) arrest after genotoxic stress. Using three cell model systems, each isogenic, we showed that either ectopic or endogenous p53 sustained a G(2) arrest activated by ionizing radiation or adriamycin. The mechanism was p21 and retinoblastoma protein (pRB) dependent and involved an initial inhibition of cyclin B1-Cdc2 activity and a secondary decrease in cyclin B1 and Cdc2 levels. Abrogation of p21 or pRB function in cells containing wild-type p53 blocked the down-regulation of cyclin B1 and Cdc2 expression and led to an accelerated exit from G(2) after genotoxic stress. Thus, similar to what occurs in p21 and p53 deficiency, pRB loss can uncouple S phase and mitosis after genotoxic stress in tumor cells. These results indicate that similar molecular mechanisms are required for p53 regulation of G(1) and G(2) checkpoints.